Assessment of Life Cycle and Environmental Impact Hotspots Associated with the Construction and Disposal of Fiberglass Reinforced Plastic Fishing (FRP) Boats in the Small-Scale Fishing Sector of India: LCA of small-scale FRP fishing boats - S. Kumar, Sreejith; P. H., Dhiju Das; Jha, Paras Nath; M.V., Baiju; Edwin, Leela; Lekshmi N., Manju (Fishery Technology, 2024)
Fiberglass reinforced plastic (FRP) is a durable thermosetting plastic widely used in small-scale marine boat building. The average life span of FRP sheathed boat is seven years, while that of FRP boat is 30 years. Once their service life ends, these boats are mostly abandoned in the coastal areas, leading to significant environmental harm. Life Cycle Assessment (LCA) evaluates a product’s entire life cycle, from raw material production to disposal, covering all intermediate stages. This study examines the LCA of boats made from FRP as a primary material and the wood/plywood boats sheathed with FRP, along the coast of Kerala, focusing on construction, use, maintenance, and disposal phases. The carbon footprint of FRP boats during their life cycle is 35.31 kg CO2 equivalent, which is considerably lower than the 63.01 kg CO2 equivalent for sheathed boats when normalised for a period of one year. Although FRP boats, require 2.4 times more materials like glass fibers and resins for construction than sheathed boats, their overall environment impact is lower due to their four times longer lifespan. The LCA findings show that resin compounds as the major contributors to environmental impacts. The study evaluated boat disposal methods in India, revealing that open burning of FRP boats generates 1253.58 kg CO2 equivalent, while landfilling reduces it to 1065.3 kg CO2 equivalent, both posing environmental risks. In contrast, sheathed boats produce a much lower carbon footprint of 77.70 kg CO2 equivalent when landfilled but have a substantially higher footprint of 596.67 kg CO2 equivalent when burned. The results underscore the pressing need for sustainable disposal methods for the end-of-life FRP fishing boats to minimize ecological damage. The results of the study also highlight the importance of material selection and waste management in reducing the environmental footprint of boat construction and disposal. These insights are crucial for promoting sustainability in small-scale boat-building yards, offering a path forward for the industry to reduce its environmental impact while maintaining the durability and longevity of the fishing boats.